Environmental system and human impact - Wright, Lawrie (London Cambridge, 1993)
The book Environmental Systems and Human Impact by Lawrie Wright, published by Cambridge University Press in 1992. This 64-page book is part of the "Update" series and provides information on the importance of the atmosphere, natural vegetation, soils, and the Earth's surface to human society. It discusses various ways in which the natural order has been modified by human actions, using specific examples from Britain and New Zealand. The book is suitable for advanced students of geography and related subjects, presenting important background material for discussions on environmental issues.